LEVEL OF QUALITY LIFE (QV), OF HYPERTENSION SENIOR CITIZEN ACCOMPANIED BY FAMILY HEALTHY PROGRAM (PHF) IN JUAZEIRO DO NORTE CITY-CEARÁ, BRAZIL (Fiep Bulletin - online, 2014)
High blood pressure iniciated to be associated with quality of life only in the 1980s. This openness has made possible the questioning with the effects of drugs on patients, what treatment improved their daily activity, and many other issues that, taken into consideration, help very certain aspects of the anti-hypertensive treatment (RIBEIRO, 2006). The objective of the study is to identify the level of quality of life for elderly reported with the levels of hypertension accompanied by the Family Health Program (PSF) in the city of Juazeiro do Norte - Ce-Brazil. The sample was composed by 24 old aged, with average age of 68.3 + 5.65. The instrument used for classification of levels of the quality of life questionnaire was the WHOQOL-focus version in Portuguese (Brazil) of the World Health Organization (1998). For classification levels of pressure was used to the chart of classification Blood Pressure (adults> 18 years) of the Brazilian Consensus of Hypertension Arterial III, 1998. Results: The analysis of data on quality of life with the group studied, showed that 47.92% of the elderly respondents are satisfied with their quality of life, while the majority 52.07% of the interviewees it is not satisfied with his quality of life and classification levels of systolic blood pressure of the elderly can see that more than 60% of the elderly are searched with indexes above normal according to the criteria established by research. To conclude, It can be argued that the group studied the levels of hypertension are being influenced in the quality of life in the physical, psychological and environmental, according to the correlation of Sperman performed with the variables studied in the group.
Keywords: Quality of Life; Hypertension; Elderly